Secure Banking Transaction and Digital Banking Using Blockchain Technology (International Journal of Innovative Research in Engineering & Management, 2022)
Internet Banking offers clients the  availability of dealing with one's assets whenever, anyplace.  In any case, any web-based exchanges will be inclined to  security dangers. Existing framework utilizes two way  validation factors(OTP) that are handily broken by digital  assailants prompting clients having their record subtleties  compromised while not having the arrangement of  aggressor's recognizable proof. Thus in this paper we  propose a versatile SIM sequential based check framework  to protect portable exchanges on cell phones with Blockchain  based waiter side secure framework. The supporter character  module(sim) chronic number is enlisted with the client's  record and in the event that a gatecrasher attempts to start an  exchange from some other sim, there emerges a befuddle of  the login certifications then framework sends area data of the  interloper to the bank. The bank then cautions the enrolled  client via mailing them the interloper's subtleties. Since the  versatile sim chronic number is remarkable to the sim and  isn't physically rather separated, there is no chance of  gatecrasher starting the exchange from another gadget,  subsequently defeating the worries connected with OTP. The  Ethereum Blockchain innovation gives server side  information base security by checking the advanced marks  during the exchange and agreement calculation for exchange  affirmation. Blockchain based security is numerically  demonstrated for secure financial exchange.
Keywords: Blockchain; Financial Exchange; Security; Portable Exchange; SIM; Framework; Validation Factors